Young British muslims : identity, culture, politics and the media - Kabir, Nahid Afrose (Edinburgh : Edinburgh University Press, 2012)
Based on 216 in-depth interviews of Muslims in Britain, examines how British Muslim youths and young adults, 15-30 years old, define their identities, their values and their culture and whether these conflict either with those of their parents or with the dominant non-Muslim British culture.
Introduction : my research observations -- The identity debate -- Muslims in Britain : an overview -- The religious and cultural dilemma -- To be or not to be British -- Is the media biased against Muslims? -- The niqab debate -- Indignation about the proposal to include shariah law in Britain -- Conclusion : a humanitarian way forward.
Includes bibliographical references (p. 219-230) and index.
ENH
Hye Trade International
Keywords: Muslims -- Great Britain -- Ethnic identity; Muslims -- Great Britain -- Social conditions; Muslim youth -- Great Britain -- Attitudes